International Journal of Emerging Electric Power Systems (De Gruyter, 2004)
IJEEPS publishes significant research and scholarship related to latest and up-and-coming developments in power systems. The mandate of the journal is to assemble high quality papers from the recent research and development efforts in new technologies and techniques for generation, transmission, distribution and utilization of electric power.